Litter decomposition dynamics in foothills agroforestry system of Indian Himalayan Shivalik range - ., Monika; Shankhwar, A.K.; Tamta, Prashansa; Singh, Vir; Prasad, Rajendra (Indian Journal of Agroforestry, 2020)
The leaf litter decomposition and dynamics of five Shivalik Himalayan foothill species [Dalbergia sisoo, Albezzia lebbeck, Tectona grandis, Bauhina varigata and Lagerstromia speciosa] on nutrient release was assessed in rice-wheat cropping system using litterbag technique. Field experiment was conducted at Agroforestry Research Centre of G.B. Pant University of Agriculture and Technology, India on mollisol. Leaf litter decay rate were estimated by using Olson’s exponential decay model. The decomposition rate constants (k) were compared in Foothills Agroforestry System of Indian Himalayan Shivalik Range and Lagerstroemia was found highest followed by Dalbergia, Albizia, Bauhinia and Tectona with 87.7, 73.8, 70.7 and 64.4 percentile. Dalbergia overruled among the five tree species that followed N>P>K nutrient release pattern. The nitrogen content in the tree leaf litter varied from the highest value (3.92%) in Lagerstroemia to the lowest (2.25%) in Tectona. The phosphorus content was highest in Dalbergia (1.67%) and lowest in Albizia (0.08%). The potassium content was found highest in Dalbergia (1.47%) while lowest (0.32%) in Tectona.